PC.108 'My Plan for the Day': Improving Handover in the Neonatal Unit. (9th June 2014) - Osmond, EA; Doerr, A; Burke, K; Evans, D
Abstract : The Plan for the Day handover tool was devised and introduced to 2 tertiary neonatal units following adverse clinical incidents deemed secondary to communication failures. Literature tells us that good communication, particularly at handover, is crucial in providing safe patient care. 1, 2 This was also identified as a key concern amongst nursing staff when surveyed about patient safety. There are currently no reports of a handover tool for neonatology, although they exist for other disciplines. 3 Graph: Nursing responders. We aimed to improve handover with a formalised, written plan for the day for each intensive care patient, with tasks designated to named individuals. A traffic light system emphasises task urgency and key areas of potential errors are regularly checked with safety prompts. The sheets were adapted after a staff survey with design simplification and re-wording of safety prompts. Important practical considerations were staff training, carrying over tasks and filing. There are challenges in measuring the effect of patient safety interventions in the neonatal setting. 4 We looked at the number of medication errors in one unit, before and after introduction of the tool. To date, the measurable effect is insignificant, this may be because there is no effect or because the study period is insufficient to show change. In an evaluation, 42% of medical staff surveyed recalled incidents when a safety prompt raised awareness of a patient safety issue, which may have otherwise have been delayed or unnoticed. Conclusion: Standardised, documented, multi-disciplinary handover documents centralise important information about infant care.